Stratospheric sulfate aerosol in and near the Northern Hemisphere polar vortex - The morphology of the sulfate layer, multimodal size distributions, and the effect of denitrification - Wilson, J. G.; Stolzenburg, M. R.; Clark, W. E.; Loewenstein, M.; Ferry, G. V.; Chan, K. R.; Kelly, K. K. (1992)
Measurements were made of stratospheric sulfate aerosols using a passive cavity aerosol spectrometer and a condensation nucleus counter on a NASA ER-2 aircraft in the Airborne Arctic Stratospheric Experiment of 1989. The problems of representative and accurate sampling and particle evaporation were explicitly addressed in the design of the inlets and reduction of the data. The measurements suggest that the sulfate aerosol is bimodal in the polar vortex above the mass mixing ratio maximum in the sulfate layer. It appears that a nuclei mode of small, newly formed particles exists in this region. A stronger case is made for a nuclei mode in the upper few kilometers of the troposphere and in the lower few kilometers of the stratosphere. This mode is probably a global phenomenon occurring in all seasons. Comparison of denitrified and nondenitrified air suggests that denitrification removes some of the larger sulfate particles.